A histological investigation of Oriental beech wood decayed by Pleurotus ostreatus and Trametes versicolor. Issue 5 (20th February 2015) - Bari, E.; Schmidt, O.; Oladi, R.; Woodward, S.
Summary Chemical, light and electron microscopic studies were carried out on wood of Oriental beech (Fagus orientalis Lipsky) decayed by the white‐rot fungi Pleurotus ostreatus and Trametes versicolor for 30, 60 and 120 days according to the modified European standard EN 113. Mass loss as well as lignin, cellulose and carbohydrate content were determined before and after fungal attack. There were no significant differences of wood mass loss and chemical composition between both fungi at the end of incubation. After each incubation period, small specimens were stained for microscopic studies. The micromorphology of fungal cell wall degradation was rather similar for both fungi. Both decreased the cell wall thickness to the same extent. The accumulation of hyphae as well as the rupture of cell walls was also similar. The occurrence of hyphae, cavities in the pits and vessel walls followed nearly the same patterns. The parenchyma cells were completely destroyed. Altogether, both fungi produced a simultaneous white rot in Oriental beech wood.